Improving HTTP Latency - Padmanabhan, Venkat (The Second International World Wide Web Conference, 1994)
The HTTP protocol, as currently used in the World Wide Web, uses a separate TCP connection for each file requested. This adds significant and unnecessary overhead, especially in the number of network round trips required. We analyze the costs of this approach and propose simple modifications to HTTP that, while interoperating with unmodified implementations, avoid the unnecessary network costs. We implemented our modifications, and our measurements show that they dramatically reduce latencies.